EFFECT OF FOREIGN DIRECT INVESTMENT ON THE ECONOMIC GROWTH: REVIEW LITERATURE - Dipali Atit Modi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Foreign direct investment (FDI) is an important driver of growth in an open and effective international economic system. Foreign Direct Investment (FDI) is critical to a host country’s economic development, especially in developing countries. The paper provides a fair review literature of various empirical and theoretical studies based on the effects of FDI on the economic growth of the host nation. The effect of FDI on economic growth is mixed, but strongly biased in favour of a substantial positive effect, though in some cases it is negative or even null. It also sees global market reach, economic autonomy, and internet access as main determinants.